Pelatihan Dan Pendampingan Penyusunan Laporan Keuangan Menggunakan Aplikasi BukuWarung Pada UMKM Usaha Kori Salon - Mariela Susana Leta; Zaenal Wafa (jurnal ABDIMAS Indonesia, 2023)
Service activities are carried out to help MSMEs in the service industry called Kori salon by making Kori salon financial reports, Kori salon financial reports are made irregularly and documented manually every day as part of its business procedures. The inability of Kori salon owners to handle bookkeeping reports is the main cause. To support MSME beauty salon businesses, it is necessary to provide training and assistance in preparing financial reports. The method used in this study is the direct support approach used in this effort to assist partners in compiling financial reports using the Bukuwarung program until it is successfully practiced. It is considered successful when partners are able to distinguish between the two states before and after receiving support. Partners recognize the value of accurately recording financial statements in the books based on the results of their actions. This exercise impacts revenue, expense and income statement accounts as well as knowledge partners and also impacts the financial statements that will be prepared in the coming year.